Promising insecticidal efficacy of the essential oils from the halophyte Echinophora spinosa (Apiaceae) growing in Corsica Island, France - Pavela, Roman; Maggi, Filippo; Cianfaglione, Kevin; Canale, Angelo; Benelli, Giovanni (Environmental science and pollution research international, 2020)
Echinophora spinosa (Apiaceae) is a psammophilous species growing along Mediterranean coastal sand dunes. This species secretes essential oils made up of monoterpenoids, phenylpropanoids, and polyacetylenes, which may represent effective, eco-friendly and safe active ingredients for the preparation of green insecticides. Based on this, in the present study, we selected a French accession of E. spinosa growing on the coastal dunes of Corsica, extracting the essential oils from aerial parts and roots by hydrodistillation. The essential oils were analyzed by GC-MS for chemical composition and screened for their insecticidal activity on three target insects, Culex quinquefasciatus, Spodoptera littoralis, and Musca domestica. The essential oil from roots was dominated by the phenylpropanoid myristicin and the monoterpene hydrocarbon terpinolene, with a minor contribution of (Z)-falcarinol. The oil from the aerial parts was characterized by monoterpenes, mainly p-cymene, a-phellandrene, and α-pinene. The root essential oil exhibited promising toxicity on the target insects, with special reference to C. quinquefasciatus larvae (LC50 = 15.7 mg L-1), while on M. domestica and S. littoralis, it showed LD50 of 38.3 μg adult-1 and 55.6 μg larva-1, respectively. Based on our findings, E. spinosa can be viewed as a new potential crop to produce insecticidal essential oils in arid salty areas. However, synergistic and antagonistic effects of the major constituents of both oils tested here deserve future research. Further studies on the efficacy of stable formulations of the E. spinosa root essential oil, with special reference to micro- and nanoformulations, are ongoing.
Keywords: Salt-Tolerant Plants; Islands; Integrated Pest Management; France; halotolerantní rostliny; Insect vector; Culex quinquefasciatus; Larvicide; insekticidy; Francie; monoterpeny; Monoterpenes; Spodoptera littoralis; Oils, Volatile; larva; Animals; Musca domestica; oleje prchavé; zvířata; Insecticides; Apiaceae; Larva; Adulticide; ostrovy